Impacto da aplicação de uma lista de verificação em round multiprofissional nos tempos de ventilação mecânica e permanência em unidades de terapia intensiva - Barcellos, Ruy de Almeida (2018)
Objective: To evaluate the impact of the implantation of a checklist during multidisciplinary daily round in the period of using invasive mechanical ventilation (MV) and permanence in the ICU. Methods: In a non-randomized clinical trial with historical controls, 466 patients submitted to MV were evaluated in a Hospital in Caxias do Sul (RS). Of this total, 235 and 231 were evaluated in the pre-intervention and post-intervention phases, respectively. The outcomes studied were SAPS-3, SOFA, frequency of infections, ICU stay, days of MV, reintubations, rehospitalizations, deaths in the ICU and hospital. Results: There was a significant reduction after the routine use of the checklist in the lenght of permanence in 37.5% (p <0.001) and 60% (p <0.001) in the time of mechanical ventilation. The frequency of pulmonary focus infection was reduced by 11.9% (p = 0.030). Conclusions: The multidisciplinarity structured through the use of checklists has an impact on the reduction of the days of use of mechanical ventilation and stay in the ICU.